2007
DOI: 10.1002/ejic.200700838
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Platinum and Palladium Complexes of Bis(trimethylsilylmethyl)tellane

Abstract: The mononuclear (telluroether)platinum and -palladium complexes cis- [ ] (3t) have been prepared from bis(trimethylsilylmethyl)tellane and bis(benzonitrile)dichloridoplatinum and -palladium and structurally characterized by single-crystal X-ray diffraction and NMR spectroscopy. The isomer distribution of the platinum complex depends on the initial molar ratio of the reactants. When [PtCl 2 (NCPh) 2 ] was used in excess, 2c was the main product. Upon increasing the initial ligand/metal molar ratio, the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…As we have observed that the Te(CH 2 SiMe 3 ) 2 ligand leads to interesting stereochemical features in case of palladium(II) and platinum(II) centers [11], it was decided to utilize this ligand also in exploration of coordination chemistry of ruthenium(II) complexes. In this work, we report the synthesis and structural characterization of [RuCl 2 (CO) 2 …”
Section: Introductionmentioning
confidence: 99%
“…As we have observed that the Te(CH 2 SiMe 3 ) 2 ligand leads to interesting stereochemical features in case of palladium(II) and platinum(II) centers [11], it was decided to utilize this ligand also in exploration of coordination chemistry of ruthenium(II) complexes. In this work, we report the synthesis and structural characterization of [RuCl 2 (CO) 2 …”
Section: Introductionmentioning
confidence: 99%
“…[10]). It is interesting to note that the 125 Te resonances of both 3b and 4b are found upfield from those of 3a and 4a (see Fig.…”
Section: Assignment Of the Resonancesmentioning
confidence: 93%
“…It has recently been reported that the palladium(II), platinum(II) [9][10][11], rhodium [12], and ruthenium(II) [13] complexes containing the Te(CH 2 SiMe 3 ) 2 (1) [9] ligand show interesting stereochemical features. In this contribution we explored the ligand properties of 1 and related unsymmetric Te(Ph)(CH 2 SiMe 3 ) 2 (2) towards the mercury(II) center.…”
Section: Tebu N N N Bu N Tementioning
confidence: 99%
See 1 more Smart Citation
“…Bis(trimethylsilylmethyl)tellane ligand forms complexes with palladium(II), platinum(II), and ruthenium(II) centres that exhibit interesting stereochemical features [14][15][16]. In this paper, we are concerned with the reaction of Te(CH 2 SiMe 3 ) 2 and RhCl 3 Á 3H 2 O.…”
Section: Introductionmentioning
confidence: 99%